(untitled) (Asian Journal of Medical and Biological Research, 2024)
Upgrading of indigenous chicken with exotic breed is an important way to improve their productivity for the traits of economic interest. The experiment was conducted to evaluate the productivity, profitability and adaptability of two up-graded dwarf chicken populations under smallholder farmers’ condition. A total of 72 birds of third generation (F3) of Dwarf-Fayoumi (IDC♂ × Fay♀) and Dwarf-Leghorn (IDC♂ × WLH♀) at 12 weeks of age were distributed to 12 farmers nearby three villages (Kewatkhali, Boyra, Sutiakhali) of Bangladesh Agricultural University, Mymensingh. Birds were reared at farmers’ house for a period of 16 weeks with same feeding and management practices. Farmers were grouped into two (6 farmers in each group) for allocating IDC♂ × Fay♀ and IDC♂ × WLH♀ upgraded genotypes. Each farmer was given six birds of same genotype. The study revealed that IDC♂× Fay♀ pullets showed earlier sexual maturity (147.50±0.76 days) and lower feed intake (74.55±0.23 g/bird/day) and thus had a better FCR (2.98±0.02) during the experimental period. The corresponding values were found 169.83±1.35 days, 76.07±0.19 g/bird/day and 3.51±0.02, in IDC♂ × WLH♀ genotype. Moreover, among the production traits considered egg mass, hen day egg production, performance efficiency index and egg feed price ratio were found higher among the IDC♂× Fay♀ pullets as 25.07±0.20 g/bird/day, 37.48±0.43%, 21.22±0.95, and 1.175±0.015, respectively. The survivability of IDC♂ × Fay♀ and IDC♂ × WLH♀ upgraded genotypes were 94.4 and 77.7%, respectively during the experimental period. Therefore, it can be concluded that the IDC♂ × Fay♀ pullets were found more productive, profitable and had better adaptability than IDC♂ × WLH♀ pullets under smallholder farmers’ management. The resultant IDC♂ × Fay♀ upgraded chicken could be utilized as mini layer under rural settings of Bangladesh. Asian J. Med. Biol. Res. 2024, 10(2), 80-88